Pengaruh Kualitas Layanan, Atmosfer Cafe Dan Kepercayaan Terhadap Loyalitas Pelanggan Pada Omah Petoeng Tulungagung - Sari, Desy Mayang; Muttaqien, Zaenul; Evasari, Aprilia Dian (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the influence of service quality, café atmosphere, and trust on customer loyalty at Omah Petoeng Tulungagung. The research employed a quantitative approach with an associative design. The population consisted of customers who had made at least two purchases, with a sample of 112 respondents selected using purposive sampling. Data were collected through a five-point Likert scale questionnaire and analyzed using multiple linear regression with SPSS version 25. The results indicate that service quality, café atmosphere, and trust have a positive and significant effect, both partially and simultaneously, on customer loyalty. Among these variables, trust shows the most dominant influence on loyalty. The coefficient of determination (R²) of 0.540 indicates that 54% of customer loyalty variation is explained by the three independent variables. These findings highlight the importance of integrating quality service, pleasant café ambiance, and customer trust in fostering long-term loyalty. The study provides practical implications for local café managers to enhance competitiveness through trust-based service strategies and customer experience management.